2014
DOI: 10.1080/21639159.2014.949372
|View full text |Cite
|
Sign up to set email alerts
|

Consumer motivations to disclose information and participate in commercial activities on Facebook

Abstract: The prevalence of social media use has significantly expanded the landscape of marketing communication and brand community management. Currently, various international brand players are beginning to develop ways of communicating with their customers on social media. This study focuses on the marketing applications of social media by examining the key motivations influencing the disclosure of personal information and participation in commercial activities of Facebook users in Hong Kong. The 566 responses were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
1
1
0
2
Order By: Relevance
“…This study also emphasizes the previous research that showed the students who contributed as a group member has a significant effect on the abilities to generate a more significant number and more innovative business ideas (Karimi, Biemans, Lans, Aazami, & Mulder, 2016). Indeed, Ng (2014) summarized some motivation among participation of commercial activities on FB: the convenience of maintaining a relationship, information benefits, and enjoyment, risks of privacy invasion, self-presentation, and social presence.…”
Section: Discussionsupporting
confidence: 74%
“…This study also emphasizes the previous research that showed the students who contributed as a group member has a significant effect on the abilities to generate a more significant number and more innovative business ideas (Karimi, Biemans, Lans, Aazami, & Mulder, 2016). Indeed, Ng (2014) summarized some motivation among participation of commercial activities on FB: the convenience of maintaining a relationship, information benefits, and enjoyment, risks of privacy invasion, self-presentation, and social presence.…”
Section: Discussionsupporting
confidence: 74%
“…Selain itu, beberapa peneliti menunjukkan bahwa pemasaran media sosial mempengaruhi preferensi merek, harga premium, loyalitas, dan ekuitas merek (Godey et al, 2016). Pembahasan lain juga telah mengemukakan bahwasanya pemasaran media sosial dan periklanan menjadikan pengguna media sosial lebih cenderung mencari informasi tentang merek yang pada akhirnya perilaku ini akan memengaruhi minat beli (Chu, Kamal, & Kim, 2013;Muk, Chung, & Kim, 2014;Ng, 2014).…”
Section: Pendahuluanunclassified
“…2014 yılında yapılan bir araştırmaya göre, Ng (2014) de Facebook işletme sayfalarının %82'sinin aktif olmadığını ve bu sayfalardaki konuşmaların %90'dan fazlasının yanıtlanmadığının altını çizmektedir ve bu sonuçların işletmelerin Facebook kullanıcılarıyla etkileşim yaratabilmek için Facebook'u nasıl doğru kullanacaklarını hala anlamaya çalıştıklarını gösterdiğini ileri sürmektedir (Ng, 2014: 366). Sosyal medya platformlarını kullanan müşterilerin %32'si hafta içi çalışma saatlerinde işletmelerden 30 dakika içerisinde bir yanıt beklemektedir; bununla birlikte, müşterilerin %57'si geceleri ve hafta sonları da aynı zaman süresinde yanıt almak istemektedir (Morgan, 2016).…”
Section: Kurumsal İletişimde Sosyal Medya Kullanımıunclassified